Pemetaan Pemahaman Konsep Analisis Pengukuran Fisika dan Mekanika Analitik Pada Mahasiswa Program Studi Pendidikan Fisika Tahun Pertama - Nur’Aini, Latiifah; Putri, Faradiva Anggraena; Setiaji, Bayu (Journal of Physics Education and Science, 2023)
Physics education study program students should have a high level of understanding of physics concepts. However, in reality the level of understanding of physics concepts for students in physics education study programs is still low. The aim of this research is to determine the distribution of students' level of conceptual understanding in the physics education study program in their first year. The research method used by the author is quantitative descriptive. This research was conducted on 43 Class C Physics Education study program students Class C of 2022 in their first year studying at Yogyakarta State University. The results of this research show that the level of conceptual understanding of Physics Education study program students in the Physics Measurement Analysis (APF) and Analytical Mechanics courses is very different in their first year of study with the average UAS score in the APF course being 2.89 and in the Analytical Mechanics course of 9.04. Therefore, alternatives are needed to improve and equalize student understanding of concepts in courses in the Physics Education study program, one of which is by improving the quality of teaching and organization in the learning process, increasing student involvement in learning physics, using effective learning methods to increase understanding. physics concepts, as well as increasing collaboration between students, lecturers and institutions in increasing understanding of physics concepts.